Mucinous Tubular and Spindle Cell Carcinoma of the Kidney: A Study of Clinical, Imaging Features and Treatment Outcomes - Xu, Xiaofeng; Zhong, Jing; Zhou, Xiumin; Wei, Zhifeng; Xia, Qiuyuan; Huang, Pengfei; Shi, Changjie; Da, Jianping; Tang, Chaopeng; Cheng, Wen; Ge, Jingping (Frontiers in Oncology, 2022)
Purpose: To describe the clinical, imaging, pathological features and oncologic outcomes of mucinous tubular and spindle cell carcinoma (MTSCC) of the kidney. Patients and Methods: Twenty-two cases of MTSCC were pathologically identified between January 2004 and April 2021 at our institution. The clinical and imaging findings, pathological features, treatment methods and outcomes of the patients were reviewed. Results: These cases included 17 women and 5 men, with a median age at diagnosis of 52.5 years. On contrast-enhanced CT, MTSCC was less enhanced than the adjacent renal parenchyma. Tumor attenuation values were 33.3±6.8HU, 44.0±9.1HU, 54.4±13.9HU and 67.1±11.8HU in the non-contrast, corticomedullary, nephrographic and excretory phases of CT, respectively. Contrast-enhanced ultrasonography and MRI also showed hypovascular features of the masses. On MRI, the tumors were isointense on T1-weighted images and slightly hypo- or hyperintense on T2-weighted images. Diffusion-weighted imaging revealed a low apparent diffusion coefficient of the tumor. The patients were managed with laparoscopic partial nephrectomy (n=5), radical nephrectomy (n=16), or robotic laparoscopic partial nephrectomy (n=1). The median follow-up time was 59.5 months. All the patients were free of local recurrence or distant metastasis. Conclusions: MTSCC is generally indolent and has favorable outcomes. The imaging features of MTSCC are generally hypovascular, which is significantly different from clear cell renal cell carcinoma. However, it is still difficult to distinguish MTSCC from other hypovascular renal tumors preoperatively because their imaging features overlap. Further studies are essential to fully characterize the features of this rare RCC variant.